Activity of acetyltransferase toxins involved in Salmonella persister formation during macrophage infection - Rycroft,J; Gollan,B; Grabe,G; hall,A; Cheverton,A; Larrouy-Maumus,G; Hare,S; Helaine,S (Nature Communications, 2018)
Non-typhoidal Salmonella strains are responsible for invasive infections associated withhigh mortality and recurrence in sub-Saharan Africa and there is strong evidence for clonalrelapse following antibiotic treatment. Persisters are non-growing bacteria that are thought tobe responsible for the recalcitrance of many infections to antibiotics. Toxin-antitoxin systemsare stress-responsive elements that are important for Salmonella persister formation,specifically during infection. Here we report analysis of persister formation of clinical invasive strains of S. Typhimurium and Enteritidis in human primary macrophages. We show that allthe invasive clinical isolates of both serovars that we tested produce high levels of persisters following internalization by human macrophages. Our genome comparison reveals that S.Enteritidis and S. Typhimurium strains contain three acetyltransferase toxins that we characterize structurally and functionally. We show that all induce the persister state byinhibiting translation through acetylation of aminoacyl-tRNAs. However, they differ in theirpotency and target partially different subsets of aminoacyl-tRNAs, potentially accounting fortheir non-redundant effect.